1975
DOI: 10.1002/ar.1091830206
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the fine structure of propylthiouracil‐induced “brown degeneration” in the zona reticularis of mouse adrenal cortex

Abstract: Propylthiouracil (6-propyl-2-thiouracil), an anti-thyroid agent, was fed to mice in a concentration equal to 0.1% of their diet for periods of 10 and 15 weeks. The cells of the inner zone of the adrenal cortex were examined with the electron microscope. In animals receiving propylthiouracil for ten weeks mitochondria were altered and the smooth endoplasmic reticulum (SER) showed a marked focal proliferation. In contrast to control animals rough endoplasmic reticulum was abundant and was frequently associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1979
1979
2009
2009

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…It is enhanced by a dietary deficiency in antioxidants, such as vitamin E, 23 or when mitochondrial damage is induced with propylthiouracil in the rodent 24 and with o, p 0 dichlorodiphenyldichloroethane (DDD) in the dog. 25 In both the propylthiouracil-induced brown degeneration in the mouse adrenal and the o, p 0 DDD intoxication of the dog adrenal, early abnormalities in mitochondrial ultrastructure (ie, swelling and loss of cristae) and ultimately their loss have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…It is enhanced by a dietary deficiency in antioxidants, such as vitamin E, 23 or when mitochondrial damage is induced with propylthiouracil in the rodent 24 and with o, p 0 dichlorodiphenyldichloroethane (DDD) in the dog. 25 In both the propylthiouracil-induced brown degeneration in the mouse adrenal and the o, p 0 DDD intoxication of the dog adrenal, early abnormalities in mitochondrial ultrastructure (ie, swelling and loss of cristae) and ultimately their loss have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, one of the figures of the reticularis cell of mouse adrenal cortex by MOORE and CALLAS (1975) shows a straight lamellar body but without any comment on it. Recently FUJITA (1977) described the same sort of body in an old mouse aged 22 months.…”
Section: Resultsmentioning
confidence: 99%
“…Specific lamellar structures of agranular endoplasmic reticulum occasionally appear in adrenal cortical cells of mice (SATO, 1967;SHELTON and JONES, 1971;MOORE and CALLAS, 1975;FUJITA, 1977), but their detailed ultrastructure has not yet been elucidated. During the course of an electron microscopic study of senile mouse adrenal glands, highly organized lamellar structures were frequently encountered in parenchymal cells of the inner zone of the cortex.…”
Section: Discussionmentioning
confidence: 99%
“…The study of Callas (1971) and the present study are, to the best of our knowledge, the only two reports on the effect of hypothyroidism on the fine structure of the zona fasciculata. A reason for the difference between the two studies may be that antithyroid agents, such as propylthiouracil, have a direct effect on the adrenal gland, in ad-dition to inhibiting thyroid function (Money, 1955;Pittman, 1971;Moore and Callas, 1975). Therefore, it is difficult to determine if reported effects are attributable to the absence of thyroid hormone or are due to a direct effect of the drug on the gland.…”
Section: Zona Fasciculata At 2 Weeks After Tpxmentioning
confidence: 99%
“…In contrast, Zarrow and Money (1949), Money (1955), and McCarthy et al (1958) found a highly significant decrease in relative weight of the adrenal gland in thiouracil-induced hypothyroidism. A drawback in interpreting some of the previous studies, which could explain in part the different results, is that antithyroid agents may have a direct effect on the adrenal gland (Money, 1955;Pittman, 1971; Moore and Callas, 1975). Thyroparathyroidectomy obviates the use of such agents; recently, we reported a decrease in relative weight of the adrenal gland in rats made hypothyroid by surgical thyroparathyroidectomy (TPX; Conran and Nickerson, 1979).…”
mentioning
confidence: 99%